Application of zinc nitrate plus chitosan favors carbon assimilation and bean (Phaseolus vulgaris L.) yield - Valencia-Vázquez, Bryan S. (2024)
Introduction. A novel alternative to increase productivity and nutrient utilization is the use of biostimulants such as chitosan, which is a product derived from the exoskeleton of crustaceans and has properties that promote growth and nutrition in crops. Objective. To evaluate the application of zinc nitrate (NZN) plus chitosan on biomass, yield, photosynthetic activity and photosynthetic pigments in green bean plants (Phaseolus vulgaris L.) for consumption of the fresh pod. Materials and methods. The experiment was conducted in a shade house located at the Centro de Investigación en Alimentación y Desarrollo (CIAD), in Delicias, Chihuahua, Mexico, during the months of August to October 2021. A completely randomized design with eight treatments and four replications was used, where zinc nitrate was applied via foliar at doses of 0, 25, 50 and 100 ppm with and without chitosan at a dose of 50 ppm. Biomass accumulation, yield, in vivo nitrate reductase enzyme activity, photosynthetic activity using Licor 6400 equipment, photosynthetic pigment content, and foliar and fruit zinc concentration were evaluated. Results. The results obtained indicated increases for the biomass variable when applying doses of 50 ppm NZN and 25 and 50 ppm NZN plus chitosan of 37.76 %, 42.39 % and 40.61 %, respectively in relation to the control without application, while for yield an increase of 45.22 % was obtained when NZN plus chitosan was applied at a dose of 25 ppm. The application of chitosan individually did not show statistical differences. Conclusions. The application of zinc nitrate plus chitosan increased total biomass production, yield and zinc content in fruit. It also favored photosynthetic activity and parameters related to photosynthetic pigments.